First year medical students' and standard precautions: The need for change - Banerjee Ankita; Mohapatra Ipsa (Elsevier, 2021)
Background: Standard Precaution (SPs) practices protect health-care workers prevent hospital-acquired infections. With Competency Based Medical Education (CBME) and early clinical exposure (ECE) implemented in the new curriculum, the first year medical students need to be aware of SPs, so as to protect themselves and the patients from these hazards. Aims & objective: To assess the knowledge of standard precautions among the medical students and find out association of knowledge with selected demographic variables. Methods and material: This cross-sectional study was done among first year medical undergraduate students of a medical college.Data was collected through google form with researcher-made questionnaire including questions on knowledge about SPs and socio-demographic variables of the study participant and their parents. Results: Response rate was 97.9%. Mean age of the participants was 19.13 ± 0.858 years; 57.7% were girls.Although 80.3% had heard of SPs but as high as 83.1% were of the opinion that "SPs were only for protection of the health-care team", 23.2% felt that it should "only be used in patients diagnosed with infection". 96.5% knew that "hand hygiene should be performed while providing care to patients", 97.2% had knowledge about respiratory and cough hygiene practices, 14.1% of them felt that "PPE can be shared". 57% of the respondents answered that "needle should be recapped after giving injections". Conclusions: Students in early clinical years were found to have a varied level of knowledge of SPs and a lot of gaps in correct understanding of required facts. Continued medical education and skill-assessment to test their knowledge, must be incorporated into their teaching curriculum before ECE, so as to minimize the risk of preventable infections.